1999
DOI: 10.1055/s-1999-14242
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenale Dopplerflußanalysen bei nierentransplantierten Patienten mit stabiler Transplantatfunktion

Abstract: The intrarenal arterial Doppler findings dependent on various extrarenal factors. Using arterial Doppler sonography to evaluate transplant kidneys it is mandatory to take into account factors such as recipient's age and hemodynamic situation. External pressure with the transducer on the graft must be avoided. Once these factors were considered the intrarenal arterial Doppler sonography of kidney transplant is a valuable diagnostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 0 publications
0
1
2
Order By: Relevance
“…A next step would be to compare intrarenal RI in patients with renal artery stenosis and the internal carotid RI to harden this suggestion. We could not show a positive correlation between renal function and RI as described in former studies (14,38). Only patients with a low FRS had a significant correlation with the transplant RI in our cohort, while Heine et al found that renal transplant recipients with a high cardiovascular risk had increased RIs.…”
Section: Discussioncontrasting
confidence: 66%
“…A next step would be to compare intrarenal RI in patients with renal artery stenosis and the internal carotid RI to harden this suggestion. We could not show a positive correlation between renal function and RI as described in former studies (14,38). Only patients with a low FRS had a significant correlation with the transplant RI in our cohort, while Heine et al found that renal transplant recipients with a high cardiovascular risk had increased RIs.…”
Section: Discussioncontrasting
confidence: 66%
“…We could also show that there is a positive association between mean kidney transplant RI and mean internal carotid artery RI. We could not show a positive correlation between renal function and RI as described in former studies [11,30]. Only patients with a low FRS had a signi cant correlation with the transplant RI in our cohort, while Heine et al found that renal transplant recipients with a high cardiovascular risk had increased RIs.…”
Section: Discussioncontrasting
confidence: 65%
“…Conversely, with colour Doppler, it is sometimes not possible to evaluate if a visualized vascular disturbance like a reduced perfusion of one renal pole is significant or due to technical limitations. It is known that diagnostic findings in Doppler ultrasound are limited when the allograft lies deep within the iliac fossa [ 33 ]. In these cases, CES can differentiate between a real and an apparent perfusion defect and spares a further examination by MRI or CT (Figure 4 ).…”
Section: Indications For Ces In Kidney Transplant Recipientsmentioning
confidence: 99%